A proposed analytical approach to estimate excess daily mortality rates in Ecuador - Fernandez-Naranjo, Raul Patricio; Vasconez-Gonzalez, Jorge; Izquierdo-Condoy, Juan S.; Landazuri, Samanta; Castillo, Diana; Ortiz-Prado, Esteban (Frontiers in Public Health, 2024)
Background The COVID-19 pandemic has proved deadly all over the globe; however, one of the most lethal outbreaks occurred in Ecuador. Aims This study aims to highlight the pandemic’s impact on the most affected countries worldwide in terms of excess deaths per capita and per day. Methods An ecological study of all-cause mortality recorded in Ecuador was performed. To calculate the excess deaths relative to the historical average for the same dates in 2017, 2018, and 2019, we developed a bootstrap method based on the central tendency measure of mean. A Poisson fitting analysis was used to identify trends on officially recorded all-cause deaths and COVID-19 deaths. A bootstrapping technique was used to emulate the sampling distribution of our expected deaths estimator μ⌢deaths by simulating the data generation and model fitting processes daily since the first confirmed case. Results In Ecuador, during 2020, 115,070 deaths were reported and 42,453 were cataloged as excess mortality when compared to 2017–2019 period. Ecuador is the country with the highest recorded excess mortality in the world within the shortest timespan. In one single day, Ecuador recorded 1,120 deaths (6/100,000), which represents an additional 408% of the expected fatalities. Conclusion Adjusting for population size and time, the hardest-hit country due to the COVID-19 pandemic was Ecuador. The mortality excess rate shows that the SARS-CoV-2 virus spread rapidly in Ecuador, especially in the coastal region. Our results and the proposed new methodology could help to address the real situation of the number of deaths during the initial phase of pandemics.